Perspektif Fiqih Minoritas Yusuf Al-Qardhawi Dalam Penentuan Awal Waktu Salat Di Daerah Kutub - Zavitri Galuh Prameswari; Mahsun (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
This study discusses the determination of the beginning of prayer times in polar regions that do not experience day and night changes as other regions normally do. The discussion will use the theory of thought from Yusuf Al-Qardhawi about minority fiqh. This study uses a library method with reference sources from books, scriptures, or articles related to the theme discussed. Furthermore, it is analyzed with qualitative data to find a complete understanding. The results are that the existing problems are in line with religious teachings and existing social realities. So with the existence of minority fiqh, it can provide a relevant legal perspective. With this discovery, it is hoped that it can contribute to minority fiqh that is by the social and cultural context that exists in Muslim minorities wherever they are.